Do Financial Advisers Influence Savings Behavior? - Burke, Jeremy (RAND Corporation, 2015)
This report reviews evidence from the research literature about whether working with a financial adviser improves savings behavior, in general, as well as saving for long-term goals, particularly retirement. Individuals who receive professional financial advice are likely to be more financially healthy, but few papers address reverse causation, limiting insights into whether advisers are causing improvements in their clients' savings behavior.